Application of Ripple Mapping with an Electroanatomic Mapping System for Diagnosis of Atrial Tachycardias. (10th October 2013) - JAMIL‐COPLEY, SHAHNAZ; LINTON, NICK; KOA‐WING, MICHAEL; KOJODJOJO, PIPIN; LIM, PHANG BOON; MALCOLME‐LAWES, LOUISA; WHINNETT, ZACHARY; WRIGHT, IAN; DAVIES, WYN; PETERS, NICHOLAS; FRANCIS, DARREL P.; KANAGARATNAM, PRAPA
Ripple Mapping: A Novel 3D EGM Display Background Three‐dimensional (3D) mapping is often used to guide ablation in atrial tachycardia (AT), but maps can be susceptible to annotation and interpolation errors. Ripple Mapping (RM) is a technique that displays electrogram time–voltage data simultaneously as dynamic bars on the surface shell to overcome these limitations. Objectives We hypothesized that RM would be superior to established 3D activation mapping. Methods CARTO‐XPTM maps of ATs were collected without any manual annotation and studied on a CARTO‐based offline RM system. Paired unannotated CARTO‐XP and Ripple Maps were presented to experienced CARTO users with limited RM training. These assessors were allowed to annotate the CARTO‐XP maps, but were blinded to conventional EP data. Results CARTO‐XP maps of AT (10 patients) were studied in RM format and the diagnosis was confirmed by entrainment in all cases and with termination of tachycardia in 9/10 cases. Blinded assessors (n = 11) reached the correct diagnosis using RM in 35/44 (80%) compared to 22/44 (50%) using CARTO‐XP (P = 0.029). The time to the correct diagnosis was also shorter with RM (136 seconds vs. 212 seconds; P = 0.022). The causes of diagnostic errors using RM (insufficient point density, particularly in low‐voltage areas, and the operator not assessing all available views) were overcome with an improved MatLab version showing both scar and dynamic bars on the same shell. Conclusion RM does not need any manual annotation of local activation time and enables rapid diagnosis of AT with higher diagnostic accuracy than conventional 3D activation mapping.